Analisis Sosiologis Novel dan Aplikasinya dalam Pembelajaran Unsur Ekstrinsik Karya Sastra di SMP - Puji Anto (Jurnal Inovasi Pendidikan Dasar, 2016)
The purpose of this study was to analyze the sociological elements of the novel and its application in the teaching of Indonesian language and literature. The method used to analyze the novel is by using descriptive method. After the authors analyzed the novel Ranah 3 Warna through elemental analysis of sociological, finally the author can draw the conclusion that the element of sociological contained in the novel Ranah 3 Warna focus of study on the theme "Mendaki Tiga Puncak Bukit" there are five elements of sociological ie social interaction with number six sentences, class social two sentences, the social group one sentence, two sentences of social problems, and social mobility of the sentence. The most dominant element is the element of social interaction that consists of six sentences. The results of this study show that social interaction is very important and is indirectly able to change the mindset at a time can change the social status of each individual. In learning extrinsic elements specifically sociological literature in school, students will be able to determine the elements of sociological through text analysis.